Tangible Interaction for Conceptual Architectural Design - Dias, J.; Monteiro, L.; Pedro, S.; Silvestre, R.; Bastos, R.; Diniz, N. (Proc ART02, “The First IEEE International Augmented Reality Toolkit Workshop”, Darmstadt, Alemanha, 2002)
This work reports and experiments a tangible mixed Reality system for Architectural Design usage scenarios, such as Conceptual Design, Client Brief, or Architectural Design Education. The system provides the means for the architect to intuitively interact with an augmented reality version of a real scale model, in normal working settings, where he can observe 3D virtual objects registered to the real ones. intuitive tangible interfaces, implemented with paddles, are used to aid design and editing tasks in /he mixed environment. By means of paddle gesturing recognition, it is possible to activate a menu, browse and choose menu options or pick, move rotate and scale 3D virtual objects, within the scale model working area. To transport the user from Augmented Reality to Virtual Environment (supporting real-time scene navigation, while in VR mode) and back, paddle gesturing recognition is also used. Complex architectural designs, described in the VRML 97 data format can be imported into our system. which provides o platform for testing new design concepts while seamlessly transporting the Architect in a truly Mixed Reality Environment: from Reality (RE) to Augmented Reality (AR)and then through Augmented Virtuality (AV), towards a full Virtual Environment (VE) and back.